Practices And Dynamics Of Multi-Cultural Communication In Curup, Rejang Lebong Regency - Hafidz Khoiril Murtadho; Rani Ramadhania Gunawan; Fitria Nurhalimah (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
This study examines the role of Islamic values-based multicultural communication in strengthening social harmony within the multicultural community of Curup, Rejang Lebong Regency, Indonesia. Increasing cultural diversity resulting from social mobility and intercultural interaction requires effective communication capable of fostering mutual understanding and maintaining peaceful coexistence. This research employed a qualitative case study approach to explore how Islamic ethical values are integrated into everyday communication practices among culturally diverse communities. Data were collected through in-depth interviews, participant observation, and document analysis involving religious leaders, traditional leaders, educators, community representatives, and local government officials selected through purposive sampling. The data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing and verification. The findings reveal that Islamic values, including ta'aruf (mutual acquaintance), tasamuh (tolerance), ta'awun (mutual assistance), shura (deliberation), justice, and mutual respect, have become essential ethical foundations for multicultural communication in Curup. These values promote inclusive dialogue, strengthen interpersonal trust, encourage collective participation, and facilitate peaceful conflict resolution among diverse ethnic groups. The study concludes that Islamic values-based multicultural communication functions as an effective catalyst for strengthening social harmony by transforming cultural diversity into social capital that reinforces community resilience and sustainable coexistence. The findings contribute to multicultural communication literature by integrating Islamic ethical perspectives into the understanding of communication practices within culturally plural societies.